2011
DOI: 10.1007/s12088-011-0140-3
|View full text |Cite
|
Sign up to set email alerts
|

Study of CTX-M Type of Extended Spectrum β-Lactamase among Nosocomial Isolates of Escherichia coli and Klebsiella pneumoniae in South India

Abstract: Data on CTX-M type extended-spectrum b-lactamase (ESBL) produced by Gram-negative bacteria by molecular methods are limited from India. This study was conducted to investigate the prevalence of CTX-M type ESBL producing Escherichia coli and Klebsiella pneumoniae from nosocomial isolates in a tertiary care hospital in southern India. A total of 179 clinical isolates of K. pneumoniae (n = 72) and E. coli (n = 107) were obtained in a period of 3 months and assessed for ESBL production phenotypically. Associated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Molecular characteriza tion revealed that 99.3% of ESBL-producing E. coli isolates (146 of 147 isolates) were positive for the blaCTx -m gene, which indicates that W«ctx-m genes commonly exist in E. coli isolates from raw meat, especially chicken. All CTX-M genes belonged to CTX-M group 1, 2, or 9, in agreement with the findings of Mohamudha Parveen et al (20). CTX-M ESBL was first discovered in a cefotaxime-resistant E. coli isolate from the fecal flora of a laboratory dog in Japan in 1986 (19); that isolate was later designated as CTX-M-1 (4).…”
Section: Discussionsupporting
confidence: 86%
“…Molecular characteriza tion revealed that 99.3% of ESBL-producing E. coli isolates (146 of 147 isolates) were positive for the blaCTx -m gene, which indicates that W«ctx-m genes commonly exist in E. coli isolates from raw meat, especially chicken. All CTX-M genes belonged to CTX-M group 1, 2, or 9, in agreement with the findings of Mohamudha Parveen et al (20). CTX-M ESBL was first discovered in a cefotaxime-resistant E. coli isolate from the fecal flora of a laboratory dog in Japan in 1986 (19); that isolate was later designated as CTX-M-1 (4).…”
Section: Discussionsupporting
confidence: 86%
“…In fact, a prelude to carbapenem resistance, as observed in this study, has been the presence of ESBLs particularly CTX-Ms. Earlier studies from our laboratory and other studies from India have shown the extensive dissemination of this gene [40] , [41] . Before the emergence of NDM-1, CTX-M-15 along with porin-loss were the reason for carbapenem-non-susceptibility.…”
Section: Discussionmentioning
confidence: 84%
“…In another study, high occurrence of ESBL in K . pneumoniae isolates was reported from South India [24]. Detection of bla CTX-M-1 and bla TEM in K .…”
Section: Introductionmentioning
confidence: 99%